Self-efficacy could change the value of the intention to quit smoking - Achmad Chusairi, Monica Ivonne Caesaria, (Opción, 2020)
This study aims to determine the relationship between self-efficacy and the intention to quit smoking. The study was conducted on 225 young adults, namely those aged 18-25 years. The data collection was done by survey methods carried out with an online system. As a result, the score of the correlation coefficient between the two variables is 0.323 with a significance level of 0.000 which indicates that there is a positive relationship between self-efficacy and the intention to quit smoking in young adults. In conclusion, there is a relationship between self-efficacy and the intention to quit smoking in young adults.